1990
DOI: 10.1002/bit.260360109
|View full text |Cite
|
Sign up to set email alerts
|

A flow‐cytometric analysis of hybridoma growth and monoclonal antibody production

Abstract: A flow cytometric kinetic study of hybridoma growth and monoclonal antibody production is presented, along with the influence of glutamine on intracellular responses such as (relative) cell size, and cell RNA and total protein content. Specific findings are: (1) RNA content remained constant throughout the growth phase, then fell drastically as the cells entered the stationary phase. Also, in stationary phase, RNA content of antibody-producing cells was higher than for those not secreting antibody. (2) The cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Entry into the stationary phase was correlated with a decrease in the mRNA for ␤-actin and recombinant APC as well as total RNA (likely due to the decrease in the major extractable component, rRNA). A similar total RNA decrease was reported by Dalili and Ollis (1990) in the analysis of a batch hybridoma cell culture by flow cytometry. The rapid decrease in the APC mRNA and cellular rRNA explains the rapid decrease in the APC production rate as the cells entered stationary phase.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Entry into the stationary phase was correlated with a decrease in the mRNA for ␤-actin and recombinant APC as well as total RNA (likely due to the decrease in the major extractable component, rRNA). A similar total RNA decrease was reported by Dalili and Ollis (1990) in the analysis of a batch hybridoma cell culture by flow cytometry. The rapid decrease in the APC mRNA and cellular rRNA explains the rapid decrease in the APC production rate as the cells entered stationary phase.…”
Section: Discussionsupporting
confidence: 74%
“…Total RNA content (Dalili and Ollis, 1990) and specific monoclonal antibody mRNA levels (Bibila and Flickinger, 1991) were roughly constant in the exponential phase and then decreased when the hybridoma cells passed from the exponential growth into the stationary phase. A correlation was also observed between the total cellular RNA content and the antibody secretion rate (Dalili and Ollis, 1990). Leno et al (1992b) investigated the relative levels of heavy-and light-chain mRNA in semicontinuous cultures with various dilution rates.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A correlation between cell size, cellular protein and antibody content with antibody secretion efficiency was seen in this study as well as suggested by previous researchers (Dalili and Ollis, 2004). The molecular regulation may have been induced by Bcl-2 to promote survival through reduction of energy-requiring cellular processes, to lower intracellular stress and create smaller cells which may be less susceptible to environmental stress.…”
Section: Molecular Effect Of Bcl-2 Over-expressionsupporting
confidence: 66%
“…Cell yields, for example, have the units number of cells per gram of substrate rather than grams of biomass per gram of substrate. Cell number yields must be used with care because the cell size (in both volume and mass) changes substantially with growth conditions (Dalili and Ollis, 1990;Frame and Hu, 1990;Ramirez and Mutharasan, 1990). Cells in a fast growing culture, for example, are on average larger than cells in a slow growing culture and more substrate is required per cell generated simply because the cells are larger.…”
Section: Introductionmentioning
confidence: 99%